Study of the Role of Rural Livelihood Programs in Rural Poverty Alleviation in Bihar (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Rural livelihood programs have been a critical component of India’s strategy to alleviate rural poverty. These programs aim to enhance income generation, provide employment opportunities, and improve the quality of life in rural areas. This review paper examines the role of various rural livelihood programs in reducing rural poverty in India, analyzing their effectiveness, challenges, and overall impact. Through an extensive review of existing literature, government reports, and case studies, this paper provides insights into the successes and limitations of these initiatives and offers recommendations for enhancing their effectiveness.